Antimicrobial Activity of Essential Oils against Streptococcus mutans and their Antiproliferative Effects. (24th May 2012) - Galvão, Lívia Câmara de Carvalho; Furletti, Vivian Fernandes; Bersan, Salete Meyre Fernandes; da Cunha, Marcos Guilherme; Ruiz, Ana Lúcia Tasca Góis; Carvalho, João Ernesto de; Sartoratto, Adilson; Rehder, Vera Lúcia Garcia; Figueira, Glyn Mara; Teixeira Duarte, Marta Cristina; Ikegaki, Masarahu; de Alencar, Severino Matias; et al.
Abstract : This study aimed to evaluate the activity of essential oils (EOs) against Streptococcus mutans biofilm by chemically characterizing their fractions responsible for biological and antiproliferative activity. Twenty EO were obtained by hydrodistillation and submitted to the antimicrobial assay (minimum inhibitory (MIC) and bactericidal (MBC) concentrations) against S. mutans UA159. Thin-layer chromatography and gas chromatography/mass spectrometry were used for phytochemical analyses. EOs were selected according to predetermined criteria and fractionated using dry column; the resulting fractions were assessed by MIC and MBC, selected as active fractions, and evaluated against S. mutans biofilm. Biofilms formed were examined using scanning electron microscopy. Selected EOs and their selected active fractions were evaluated for their antiproliferative activity against keratinocytes and seven human tumor cell lines. MIC and MBC values obtained for EO and their active fractions showed strong antimicrobial activity. Chemical analyses mainly showed the presence of terpenes. The selected active fractions inhibited S. mutans biofilm formation (P < 0.05 ) did not affect glycolytic pH drop and were inactive against keratinocytes, normal cell line. In conclusion, EO showed activity at low concentrations, and their selected active fractions were also effective against biofilm formed by S. mutans and human tumor cell lines.